Linking Arenas: structuring concepts in the study of politics and protest. (4th March 2021) - Jasper, James M.
ABSTRACT: An arena is a familiar, common-sense word to specify what constrains and enables human actors, or players, in politics, in the sense of the places where they do politics. It joins a long list of similar concepts – institutions, political opportunity structures, fields, spaces, worlds – that reflect the intuition that no political players, even the most powerful, can get exactly what they want all the time. They face an environment containing various settings and many other players. An arena is a tighter concept than most of these other terms, partly because it is used alongside the idea of players who operate in those arenas. It represents physical places where decisions are made, with something at stake, although it includes not only physical constraints and aids but any rules and customs usually applied. This paper shows how it is related to broader concepts, especially fields and spaces, which represent aggregates of arenas or of players.